Single haptic iris fixation of posterior chamber intraocular lens - Vellam R Vivekanandan; Thamizhselvi Dhanaseelan; Merlin Benzy; Rengaraj Venkatesh; Varshini Odayar (Indian Journal of Ophthalmology, 2023)
Single haptic iris fixation technique is used where there is a loss of 6 clock hours anterior capsular support. It helps the anterior segment surgeon to fix the intraocular lens to the iris on the side of absent capsular support and place the other haptic over the capsular support. A 10-0 polypropylene suture on a long-curved needle is only used to take a suture bite on the side of capsule loss. Meticulous automated anterior vitrectomy is done. Then, the suture loop below the iris is taken out and the loops are twirled multiple times around the haptic. The leading haptic is then gently glided behind the iris, and the trailing haptic is gently placed on the other side using forceps. The suture ends are trimmed and internalized into the anterior chamber and then externalized through the paracentesis using a Kuglen hook, and the knot is tied and secured.